2016
DOI: 10.1371/journal.pone.0161214
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasma urealyticum Causes Hyperammonemia in an Experimental Immunocompromised Murine Model

Abstract: Hyperammonemia syndrome is an often fatal complication of lung transplantation which has been recently associated with Ureaplasma infection. It has not been definitely established that Ureaplasma species can cause hyperammonemia. We established a novel immunocompromised murine model of Ureaplasma urealyticum infection and used it to confirm that U. urealyticum can cause hyperammonemia. Male C3H mice were pharmacologically immunosuppressed with mycophenolate mofetil, tacrolimus and oral prednisone for seven day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…Similar with results of our previous study with U. urealyticum [8], none of the mice not receiving pharmacologic immunosuppression challenged IT/IP with U. parvum developed elevated plasma ammonia concentrations, while immunosuppressed mice challenged with U. parvum IT/IP or IP had higher plasma ammonia levels (up to 1,000 μmol/L) than vehicle-challenged controls (p<0.001). Additionally, in this study, we were able to measure plasma ammonia concentrations of a few mice that died just before the experimental endpoint and found ammonia concentrations up to 1,000 μmol/L or greater.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar with results of our previous study with U. urealyticum [8], none of the mice not receiving pharmacologic immunosuppression challenged IT/IP with U. parvum developed elevated plasma ammonia concentrations, while immunosuppressed mice challenged with U. parvum IT/IP or IP had higher plasma ammonia levels (up to 1,000 μmol/L) than vehicle-challenged controls (p<0.001). Additionally, in this study, we were able to measure plasma ammonia concentrations of a few mice that died just before the experimental endpoint and found ammonia concentrations up to 1,000 μmol/L or greater.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, we established an immunocompromised experimental mouse model in which we showed that U. urealyticum ATCC 27618 can cause hyperammonemia [8]. Here, we show that a clinical U. parvum isolate can cause hyperammonemia using the same model.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Pharmacologically immunosuppressed mice challenged intratracheally (IT) or intraperitoneally (IP) with U. urealyticum were found to have significantly higher plasma ammonia concentrations then those challenged with a negative vehicle‐control. Interestingly, U. urealyticum IT/IP challenged immunocompetent mice did not develop hyperammonemia . A follow up study using U. parvum found similar results, with hyperammonemia only seen in immunosuppressed mice, not immunocompetent mice, challenged with U. parvum IT/IP .…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, two prospective patients identified with hyperammonemia syndrome and U. parvum infection responded to antimicrobial treatment . Subsequently, a murine model was used to confirm that U. urealyticum and U. parvum infection could cause elevated plasma ammonia concentrations in pharmacologically immunocompromised mice …”
Section: Introductionmentioning
confidence: 99%